15 Cambios en los paradigmas del sector forestal de América Latina - Galloway, Glenn; Kengen, Sebastiao; Louman, Bastiaan; Stoian, Dietmar; Mery, Gerardo; Carrera Gambeta, Fernando; Córdoba, Raúl; González, Luis; Trevin, Mery (2016)
5 ilus. 6 tab. 88 ref. 35 pág.